Value at risk simulation in a fixed return stock portfolio using the Monte Carlo simulation model The concept of a bond portfolio (Journal of Accounting and Financial Studies ( JAFS ), 2021)
This research aims to predict the value of the maximum daily loss that the fixed-return securities portfolio may suffer in Qatar National Bank - Syria, and for this purpose data were collected for risk factors that affect the value of the portfolio represented by the time structure of interest rates in the United States of America over the extended period Between 2017 and 2018, in addition to data related to the composition of the bonds portfolio of Qatar National Bank of Syria in 2017, And then employing Monte Carlo simulation models to predict the maximum loss that may be exposed to this portfolio in the future. The results of the Monte Carlo simulation showed the possibility of decreasing the value at risk in the future due to the decrease in the intensity of fluctuations in medium-term interest rates across maturity periods.